Auto-lysed yeast and yeast extract effects on dry matter intake, blood cells counts, IgG titer and gene expression of IL-2 in lactating dairy cows under heat stress (Acta Scientiarum. Animal Sciences, 2020)
The objective of this study was to assess the effects of auto-lysed yeast and yeast extract on performance and immune responses of cows in hot climate in the early lactation period. Twenty five lactating dairy cows randomly assigned to 5 groups and 5 replicates. Cows received basal diet with or without auto-lysed yeast (20 or 40 g/d/head) or yeast extract (20 or 40 g/d/head) as on top-dressed. There were no differences for daily dry matter intake, milk production milk fat and the counts of red blood cells and white blood cells among treatments (p > 0.05). There were significant differences among treatments for immunoglobulin G (IgG) level, lymphocyte and neutrophil percentages. Yeast extract had no effect on IgG level, but auto-lysed yeast increased IgG level and neutrophil percentage and decreased lymphocyte percentage (p < 0.05). The highest relative interleukin-2 gene expression was for cows received auto-lysed yeast at the level of 40 g/d/head. Yeast extract had no significant effect on interleukin-2 gene expression as compared to the control group. It was concluded that auto-lysed yeast at the level of 40 g/d/head had no effect on performance, but it could positively influence on immune response of lactating dairy cows in hot climate during early period of lactation.